Unveiling the layered structures of youth work - Nuutinen, Ana; Mikkonen, Enni (Routledge, 2022)
This article is based on a case study involving the youth work department in the City of Kemi and the artist-researchers from the University of Lapland in Rovaniemi in Northern Finland. During the project, activities related to youth work promoting youth’s wellbeing and preventing their marginalisation have revealed to be multi-layered and complex by nature. Layers in this context refer to the organizations and their physical spaces (e.g. street address) as well as virtual spaces (e.g. discord, social media channels), Kemi service providers (e.g. Detective youth work, Ohjaamo Kemi, Rehabilitative work) and youth workers as well as the young people themselves. By looking at the plurality contained in those layers, we aim at reposition agendas and actions related to youth work and collaboration with stakeholders therein towards a more systemic - rather than individualistic - orientation that seeks to understand the complexities of circumstances different youth live in. Three types of layers will be observed. Observation from the bird's eye view aims to identify the whole and its parts, as well as the different interactions between them. In the frog, or grass-root, perspective the overall picture will be formed from separately observed sub-views “as you go”. The rhizome perspective seeks to identify structures and/or functions that lie beneath the surface. Methodically, the layer-related observations will be made by applying the theory of space syntax (Hillier 1996, 2007) and the concept of rhizome (Deleuze & Guattari 1987). Research on youth work (e.g. Mertanen 2020) will add a critical perspective to these observations. In addition, art-/design-based methods are used to support the theoretical approach. Experimental prototypes (provotypes) are manufactured to look critically at, for example, the layers and the “traffic” between them, or to unveil functions hiding under the surface. This study describes the components and actors of stakeholder and youth interaction with a particular interest in visibilising ...